The Petrology and Volcano-Stratigraphy of The Muria-Peninsula High-K Volcanic Rocks, Central Java, Indonesia - Sri Mulyaningsih; Sutikno Bronto; Arie Kusniadi; Lilis Apriyanti; L. Budiyanto; Danis Agoes Wiloso (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
The Muria-Peninsula is a Quaternary volcano located in the northern Sunda arc. Its activity was controlled under high potassic and very high potassic magma series resulting in leucite-rich trachyte and pyroxene-rich basaltic-andesite. It is a strato-type volcano that is composed of lava, breccia, and tuff layers, and some dikes have some volcanic craters and maars varying in age and composition. The study area is covering the volcanoes of Muria, Genuk, and Patiayam. This paper aims to describe the petrology, mineralogy, and volcano-stratigraphy of the different volcanic materials. The data and materials were sourced from the primary and secondary data. The methods are field mapping, stratigraphy measurements, collecting samples, thin section analyses, and major element geochemistry using X-Ray fluorescence (XRF). The results describe two groups of volcanic rocks consisting of pyroxene-rich andesitic-basaltic volcanic materials and leucite-rich trachytic volcanic materials. Augite presents in the andesitic basalt together with small grains of olivine and a few anorthite and foid minerals. Aegirine (Na-Pyroxene) is present in the leucite-rich trachyte that is often associated with biotite and hornblende. Na-Ca Plagioclase such as labradorite-andesine is often present in the basaltic-trachy-andesite that is usually rarely leucite. The major elements show high-K volcanic rocks with % K2O is 4-5.9% and very high-K volcanic rocks (with % K2O is between 6-8.24%) and low-K volcanic rocks that contain % K2O is 2-3,9%. There are two groups of high-K to very high-K volcanic materials consisting of silicic-rich volcanic materials (~57-64% of SiO2) and low-silicic volcanic materials (~46-50%). The TAS diagram identifies tephrite, phonolite, and trachyte. Stratigraphic data identifies calcareous sediments of the Bulu Formation as the basement rocks of the Muria trachyandesite. Beds of pumice-rich volcanic breccia of the Ujungwatu Formation are the basement rocks of the basanite-tephrite of the Genuk Volcano, and the tuff of the Ujungwatu is also exposed consisting of the basanite-tephritic-phonolite of the Patiayam Volcano. The leucite-like feldspars are very common in the andesite lava and dikes that compose the crater of Muria. Most of the Muria volcanic materials are rarely in leucite, while some maars contain pumice-rich pyroclastic flows and basaltic lava. The results of the major elemental analysis of the Muria materials indicate that the rock tends to be of medium to high K affinity (~2% K2O). The Genuk and older Muria are consisting of leucite-rich tephrite-phonolite. It was two periods of magmatic series developed in the Muria-Peninsula that was resulting in the high-K to very high-K magmatism and the medium K Kalk-alkaline magmatism.